Associating Physical Activity Levels with Motor Performance and Physical Function in Childhood Survivors of Acute Lymphoblastic Leukemia - Hung, Stanley H. (Physiother Can, 2017)
Purpose: This cross-sectional, observational study investigated whether physical activity (PA) levels are associated with motor performance and physical function in children after treatment for acute lymphoblastic leukemia (ALL). Method: Participants aged 8–13 years who had completed treatment for ALL (3–36 months post-treatment) were tested at their oncology long-term follow-up appointment at the British Columbia Children's Hospital. PA level was measured using the Physical Activity Questionnaire for Older Children (PAQ-C). Motor performance was measured using the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition, Short Form (BOT-2 SF), and physical function was measured using the 6-minute walk test (6MWT). Results: Thirteen children completed testing. PAQ-C scores were not associated with BOT-2 SF or 6MWT performance. Eleven children (85%) performed below the norm for the 6MWT. Children with elevated body mass index had poorer 6MWT but similar PAQ-C scores. Conclusion: PA was not found to be associated with motor performance and physical function. Participants who were overweight or obese had poorer 6MWT performance, which may indicate the need for closer monitoring of post-treatment weight status and physical function in the oncology follow-up setting.